Continuous Educational Training in children’s education: meanings of a pedagogical supervisor (Research, Society and Development, 2018)
This article is an excerpt of a research performed with a pedagogical supervisor from children’s education on the public educational system at Mossoró city (Rio Grande do Norte state – Brazil), which title is “The meanings embodying oneself as a pedagogical supervisor: reflections of a children’s education professional”. This study aims apprehending the meanings embodied by a supervisor about the continuous educational in order to qualify children’s education professional. It is based both theoretically and methodologically on Sociohistorical Psychology and on dialectical and historical materialism, for we understand the importance of this approach/method to apprehend the meanings as a process mediated by continuous educational training in the context of his/her social and professional work. Regarding data production, we adopted the reflexive interview procedure. The interpretative analysis of the produced data was carried out by the means of proposal named “Cores of Meaning”. We comprehend that the senses embodied by the supervisor reveal the continuous educational training as a mediator of situations experienced on his/her professional reality, on the relationship with the other professionals. Therefore, the process of continuous educational training fosters the constitution of new senses for the mediation of his/her activity.